Description of Enhanced-Efficiency Fertilizers for Use in Vegetable Production - Luther Carson; Monica Ozores-Hampton (EDIS)
In response to the Federal Clean Water Act of 1972 and the Florida Restoration Act of 1999, a series of best management practices (BMPs) was implemented to improve surface and ground water quality. BMPs are cultural practices that, when implemented as a plan, help reduce the environmental impact of production while maintaining yield and quality. One of these BMPs includes the use of controlled-release fertilizer, which is an enhanced-efficiency fertilizer. This publication describes the common enhanced-efficiency fertilizers and the factors affecting their use in Florida vegetable production. This 9-page fact sheet was written by Luther Carson and Monica Ozores-Hampton, and published by the UF Department of Horticultural Sciences, October 2014.